Speckle tracking echocardiography for evaluation of myocardial functions before and after mitral valvuloplasty in dogs - Fukuzumi, Sho; Mandour, Ahmed S.; Farag, Ahmed; Yoshida, Tomohiko; Nishiura, Akitsugu; Yotsuida, Hideki; Yaginuma, Yota; Matsuura, Katsuhiro; Tanaka, Ryou (Frontiers in Veterinary Science, 2024)
BackgroundMyxomatous mitral valve disease (MMVD) is the most common acquired heart disease in dogs. Mitral valvuloplasty (MVP) addresses regurgitation, but the pre- and postoperative changes in myocardial function remain uncertain.ObjectivesThis study evaluated myocardial motion before and after MVP using two-dimensional speckle-tracking echocardiography (2D-STE).AnimalsEight client-owned dogs undergoing MVP for MMVD.MethodsMyocardial deformation was assessed by 2D-STE before surgery and at 1- and 3-months post-surgery. Measurements included left ventricular global longitudinal strain (GLS), global circumferential strain (GCS), global radial strain (GRS), cardiac twist, and right ventricular free wall GLS (RVFW-GLS).ResultsPostoperative decreases were observed in left ventricular internal dimensions, left atrial size, and early diastolic myocardial velocity, with an increase in peak late diastolic velocity. LV-GLS decreased at 1 month (−14.4%) and 3 months (−16.3%) compared to preoperative values (−24.4%) (p = 0.0078, p = 0.015). GCS decreased at 1 month (−12.9%) and 3 months (−14.8%) compared to preoperative values (−21.7%) (p = 0.0078). GRS decreased at 1 month (27.7%) and 3 months (32.0%) compared to preoperative values (67.7%) (p = 0.0078). No significant changes were observed in RVFW-GLS. Peak systolic twist increased at 3 months (9.1° vs. 4.9°, p = 0.039). Peak systolic apical rotation showed an upward trend at 3 months (p = 0.109). Left ventricular twist was mildly affected by LVIDd, LVIDDN, and sphericity index (R2 = 0.187, p = 0.034; R2 = 0.33, p = 0.0029; R2 = 0.22, p = 0.019).Conclusions and clinical importancePostoperative myocardial motion approached reference values, indicating significant improvement, particularly in left ventricular twisting motion. These findings highlight the positive impact of surgery on cardiac function in dogs with MMVD.